The Influence of Transformational Leadership, Compensation, and Job Burnout on Employee Performance PT. POS Indonesia KCU Semarang (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The purpose of this study was to determine the effect of transformational leadership, compensation, and job burnout on employee performance at PT. POS Indonesia KCU Semarang. The population in this study were permanent employees of PT. POS Indonesia KCU Semarang. Sampling in this study used saturated sampling. Data analysis in this study was multiple linear regression and hypothesis testing in the study used methods and data processing using IBM SPSS Statistics 25. The results showed that transformational leadership had a positive and significant effect on employee performance, compensation had a positive and significant effect on employee performance and Job Burnout had a positive and significant effect on Employee Performance at PT. POS Indonesia KCU Semarang.
Keywords: Transformational Leadership; Compensation; Job Burnout; Employee Perfomance